Teredus opacus Habelmann, 1854 from Sochi region – the frst record in Russia and the Caucasus, with notes on some other representatives of teredids (Coleoptera: Teredidae) - A.I. Miroshnikov (Кавказский энтомологический бюллетень)
A representative of the family Teredidae, Teredus opacus Habelmann, 1854, has been discovered for the first time in Russia on the Black Sea coast in Krasnodar Region. It was previously considered endemic to Central and Southern Europe and is one of the rarest beetle species in the European fauna. A very old record of Teredus cylindricus (A.G. Olivier, 1790) in Oryol Region, Russia, unaccounted for in the subsequent works, is indicated. Te ecological features of these species are considered along with other taxa of the Teredidae. Another European species of the family is presented – Oxylaemus cylindricus (Creutzer in Panzer, 1796), known from individual records in the North-West Caucasus. A key to species of the tribe Teredini of the fauna of Russia is given.